Obtaining reliable embodied carbon values for geosynthetics. Issue 5 (26th August 2015) - Raja, J.; Dixon, N.; Fowmes, G.; Frost, M.; Assinder, P.
Abstract : ABSTRACT: Changing climate and the damaging effects of carbon dioxide (CO2 ) on the environment, has led to awareness throughout the construction industry of the need to deliver more sustainable solutions. Robust and rigorous carbon footprinting procedures for assessing solutions and projects can help to identify where action can be taken to reduce CO2 emissions. It also promotes the marketing of those solutions and methods that produce lower CO2 emissions. Geosynthetics often provide a cost-efficient alternative to more 'traditional' construction techniques. Recently, work by the Waste and Resources Action Programme in the UK has shown that geosynthetic solutions can also produce much lower CO2 emissions. However, there are still questions as to the reliability of such calculations. Although the methodologies employed are relatively consistent worldwide, the accuracy of the embodied carbon data available for use in calculations remains uncertain. Geosynthetic products are not specifically included in the embodied carbon construction materials databases most commonly employed in Europe, and often generic values for polypropylene and polyethylene are used. This paper presents a study in which the embodied carbon data for geosynthetic products was calculated using first-hand manufacturing process data. The values calculated for two categories of geosynthetics were considerably lower than commonly employed database values. Nonwoven geotextiles had an average embodied carbon value of 2.35 tCO2 e/t, with values for example geogrids of 2.97 tCO2 e/t for extruded and 2.36 tCO2 e/t woven.